2018
DOI: 10.2174/1874210601812010061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3D Scanning Versus 2D Photography for the Identification of Facial Soft-Tissue Landmarks

Abstract: Background:Three dimensional facial scanning is an innovation that provides opportunity for digital data acquisition, smile analysis and communication of treatment plan and outcome with patients.Objectives:To assess the applicability of 3D facial scanning as compared to 2D clinical photography.Materials & Methods:Sample consisted of thirty Caucasians aged between 25 and 50 years old, without any dentofacial deformities. Fifteen soft-tissue facial landmarks were identified twice by 3 observers on 2D and 3D imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…3 Even though quantitative studies exist in the literature, these devices have barely been compared in a qualitative manner. 24,27,28 Stebel et al qualitatively compared 2D and 3D stereophotogrammetry images to evaluate nasolabial aesthetics and found that SPG was more reliable and informative than 2D imaging, which corresponds with our findings. 28 However, in our study, the observers were more confident with LS than with 2D images, in contrast with the findings of Zogheib et al 24 The main limitations of this study are related to laser scanning, such as motion artefacts in the orbital region related to the blinking reflex, the application of chin support, and a long capture process, which might have influenced the results.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…3 Even though quantitative studies exist in the literature, these devices have barely been compared in a qualitative manner. 24,27,28 Stebel et al qualitatively compared 2D and 3D stereophotogrammetry images to evaluate nasolabial aesthetics and found that SPG was more reliable and informative than 2D imaging, which corresponds with our findings. 28 However, in our study, the observers were more confident with LS than with 2D images, in contrast with the findings of Zogheib et al 24 The main limitations of this study are related to laser scanning, such as motion artefacts in the orbital region related to the blinking reflex, the application of chin support, and a long capture process, which might have influenced the results.…”
Section: Discussionsupporting
confidence: 88%
“…24,27,28 Stebel et al qualitatively compared 2D and 3D stereophotogrammetry images to evaluate nasolabial aesthetics and found that SPG was more reliable and informative than 2D imaging, which corresponds with our findings. 28 However, in our study, the observers were more confident with LS than with 2D images, in contrast with the findings of Zogheib et al 24 The main limitations of this study are related to laser scanning, such as motion artefacts in the orbital region related to the blinking reflex, the application of chin support, and a long capture process, which might have influenced the results. 1,27,29 To overcome these limitations, we recommend utilizing marker-free fixed 3D stereophotogrammetric systems such as the 3D Vectra ® H1, 3dMDface TM (3dMD LLC, Atlanta, USA) and Di3D TM (Dimensional Imaging, Glasgow, UK) imaging systems.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(11) According to Zogheib et al, 3D imaging could enable angular measurement of human face as much as a photograph. (12) Through these current studies, 3D imaging could be used to study whether surgical techniques have the desired effect on the nose.…”
Section: Discussionmentioning
confidence: 99%
“…To offset these drawbacks, advances have been made in the capture and analysis of digital 3D photos, also known as stereophotogrammetry, which offers great development potential in the diagnosis and treatment of facial deformities (Zogheib et al, 2018). These captures can analyze facial morphology and thus craniofacial growth, changes in soft tissues after facial surgery, planning studies and digital surgical simulation, among others (Vittert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%